Representation of yoga postures based on joint angle values along with Range of motion limitations of joints to classify time series yoga - Chezhiyan, Ponmozhi; M, Anisha (International Journal of Psychosocial Rehabilitation, 2020)
The practice of yoga poses, or asanas, was developed as an approach to align, strengthen, and balance the structure of the body. Further, it has been used to enhance dynamic control of core stabilizing muscles to reduce lower back pain (LBP) and spinal flexibility. Yoga postures comprise simple body movements such as standing, sitting, forward and backbend, twist, inversion, and lying down in supine position. In this paper proposes a method to classify yoga asana postures based on joint angles. Not every joint is involved in all asanas. Set of joints that contributes a lot for a particular asana and their range of motion has studied in order to classify asanas based on the joints involved. Applicability using BVH and softmax classification has been discussed.